Learning to Beat the Shock Clock: A Low-Fidelity Simulation Board Game for Pediatric and Emergency Medicine Residents - E. Page Bridges; Catherine E. Foster; Dan B. Park; Kathy L. Lehman-Huskamp; Dan W. Mark; Rachel E. Tuuri (Association of American Medical Colleges, 2019)
Introduction Resident physicians may have difficulty with identifying and managing pediatric septic shock due to limited patient encounters. Simulation-based interventions can enhance competency. We developed a low-fidelity tabletop simulation game to teach pediatric septic shock and compared residents' knowledge of and comfort with recognition and management of septic shock. Methods Pediatric and emergency medicine residents participated in an education session involving a low-fidelity, tabletop simulation in which they managed two simulated pediatric patients with septic shock. The two patients were a 12-year-old healthy male with cold shock due to a urinary tract infection and a 5-year-old female with a history of leukemia who developed warm shock due to pneumonia. Because this session was presented as a board game rather than high-fidelity simulation, learners focused on decision making rather than the mechanics of procedures. Residents completed a survey and a knowledge-based test before and after this session. Results Twenty-three pediatric and nine emergency medicine residents participated. Correct responses for the preintervention test were 71%, compared with 83% postintervention. The difference in rates was 12% (95% confidence interval, −0.17 to −0.07; p < .0001). Residents rated this modality as being more useful than lectures or reading and as equivalent to bedside teaching and high-fidelity simulation. Discussion Our pilot low-fidelity simulation improved resident knowledge and comfort with pediatric septic shock care. Further studies are needed to address the impact of low-fidelity simulations on patient outcomes.